(untitled) (Global Business Management Review (GBMR), 2022)
Presumably, World faces sundry climate challenges contains often sporadic floods, ruthless droughts, severe thunder storms, infrequent rains, swamped plains and barren land, water assimilation & water scarcity. The broad aim of this study is to observe theoretically and empirically the intensity of climate changing events in Pakistan in general and Khyber Pakhtunkhwa (KP) in particular. The data on environmental analysis demonstrates that climate change put harsh impacts on crop production in the southern part of the province. For more robust analysis, an econometric model and the panel data regression method is also used, where the data covering the period from 1980 to 2010. The empirical results also confirm that climate change has some strong effect on the crop production in the southern part of the province in the country. The results further reveal that the central region faces relatively a moderate impact while, the northern part has a positive climate impact in terms of crop production. In light of the findings of the study some suggested policy measures would indubitably help the policy makers.